Experimentos com o arduino® nas aulas de física - Silva, Andreia Paulino da (Universidade Federal Rural do Semi-Árido, 2019)
Experimentation is fundamental in the teaching of physics since it guarantees the student to do, to handle and mainly to understand how the process of formulation of physical laws occurs through the scientific method. From the earliest times, when a physics was still titled Natural Philosophy, having as one of its pioneers Galileu Galilei, that experimentation becomes a fundamental piece for the verification of scientific truths. Within the teaching of physics, it is combined with the didactic laboratory, which in turn evolved according to the prevailing education paradigm. Its importance within the laboratory is in the acquisition and processing of data collected by some electronic device. In this work, we use the Arduino® platform to collect such data by presenting free software, having a low cost-benefit ratio (in relation to commercial kits), for its versatility and ease of programming. Your microcontroller can be easily used in other physics experiments, differing from commercial laboratory kits that are only used for certain experiments in which they were designed. We will show experiments such as free fall, simple pendulum and mass-spring system, many of these models used in physics classes using the computer and Arduino® board for acquiring and processing this data, thus making student interaction with technology, classes of physics more dynamic and attractive.
Keywords: Ensino de física; Experimentação; Computador; Arduino®; Physics teaching; Experimentation; Computer; Arduino®; CIENCIAS EXATAS E DA TERRA::FISICA